Utilization of Sasa borealis seeds by Japanese field mouse: discovery of small-seed caching - Suzuki, Hanami; Kajimura, Hisashi (Frontiers in Ecology and Evolution, 2023)
Bambusoideae are well-known for their large-scale flowering, seeding, and death events that occur after a vegetative phase that can often last for decades. These events are a valuable resource for many animals. Their mast seeding, in particular, affects rodent populations although the causal relationship between them is speculative. Moreover, the species of animals that utilize this resource also remains unclear. Therefore, this study aimed to examine the interaction between mast seeding plants and animals by conducting a feeding test using the seeds of a dwarf bamboo species (Sasa borealis) at different seasons and in different forest types. The results revealed that two mouse species, Apodemus speciosus and A. argenteus, utilized the seeds. They both predated as well as removed and sometimes buried the seeds, exhibiting small-seed caching behavior. Furthermore, A. speciosus was found to exhibit higher seed predation at covered sites and switching to removal behavior at the more exposed, open sites, while A. argenteus showed no distinguishable trends. Additionally, A. speciosus utilized the seeds less frequently in fall than in summer, suggesting a shift in diet towards acorns when available. Collectively, the results of this study provide novel insights into the interaction between mast seeding plants and the animals that utilize them.